Adrenoceptors of the medial septal area modulate water intake and renal excretory function induced by central administration of angiotensin II - Saad, W.A. [UNESP]; Guarda, I.F.M.S.; Camargo, L.A.A. [UNESP]; Santos, T.A.F.B.; Simões, S.; Saad, Willian A. (Associação Brasileira de Divulgação Científica (ABRADIC), 2002)
We investigated the role of alpha-adrenergic antagonists and clonidine injected into the medial septal area (MSA) on water intake and the decrease in Na+, K+ and urine elicited by ANGII injection into the third ventricle (3rdV). Male Holtzman rats with stainless steel cannulas implanted into the 3rdV and MSA were used. ANGII (12 nmol/µl) increased water intake (12.5 ± 1.7 ml/120 min). Clonidine (20 nmol/µl) injected into the MSA reduced the ANGII-induced water intake (2.9 ± 0.5 ml/120 min). Pretreatment with 80 nmol/µl yohimbine or prazosin into the MSA also reduced the ANGII-induced water intake (3.0 ± 0.4 and 3.1 ± 0.2 ml/120 min, respectively). Yohimbine + prazosin + clonidine injected into the MSA abolished the ANGII-induced water intake (0.2 ± 0.1 and 0.2 ± 0.1 ml/120 min, respectively). ANGII reduced Na+ (23 ± 7 µEq/120 min), K+ (27 ± 3 µEq/120 min) and urine volume (4.3 ± 0.9 ml/120 min). Clonidine increased the parameters above. Clonidine injected into the MSA abolished the inhibitory effect of ANGII on urinary sodium. Yohimbine injected into the MSA also abolished the inhibitory effects of ANGII. Yohimbine + clonidine attenuated the inhibitory effects of ANGII. Prazosin injected into the MSA did not cause changes in ANGII responses. Prazosin + clonidine attenuated the inhibitory effects of ANGII. The results showed that MSA injections of alpha1- and alpha2-antagonists decreased ANGII-induced water intake, and abolished the Na+, K+ and urine decrease induced by ANGII into the 3rdV. These findings suggest the involvement of septal alpha1- and alpha2-adrenergic receptors in water intake and electrolyte and urine excretion induced by central ANGII.
Keywords: alpha-Adrenoceptors; Angiotensin II; Water intake; Sodium; Potassium; Water excretion; Medial septal area